DTap vaccination uptake during pregnancy: Pregnant women-focused and health professionals-focused predictors in the Veneto Region (Italy). Issue 47 (16th November 2021) - Cappozzo, Francesco; Dal Zotto, Alessandra; Scollo, Marcello; Bernardini, Daniele; Maria Dal Zotto, Anna; Bonvecchio, Lucia; Tognetto, Gabriella; Marinangeli, Simonetta; Negrello, Chiara; Lanza, Paola; Cocco, Andrea; Falivene, Patrizia; et al.
Abstract: Background: Despite recommendations, the uptake of dTap maternal vaccination is still low in many countries. The reasons for this must be investigated both on the patient's and the healthcare professionals' sides. Methods: A record linkage study was performed linking Birth Assitance Certificates and dTap mothers' vaccination records (5183 deliveries) to describe the influence of socioeconomical and obstetrical-gynecological factors after the recommendations concerning dTap vaccination in pregnancy issued by the Italian Ministry of Health (August 2018). An interview was also administered to a subgroup of 656 new mothers on the occasion of the first vaccination of their newborns, in order to assess the dTap vaccination advice received from maternal care providers during pregnancy. A generalized linear model (binomial family, log link) was implemented to give a correct estimate of the mother's relative risk of being vaccinated. Results: Several pregnant women-focused factors are evident, but the most important ones are related to maternal care providers' practices: after mutual adjustment, the explicit advice towards dTap maternal vaccination given by the Obstetrician-Gynecologist or the Midwife is associated with a 12-fold increase in the dTap coverage. Conclusions: Multiprofessional training is essential to make Obstetricians-Gynecologists and Midwives more confident in recommending dTaP maternal immunization.